2011
DOI: 10.1103/physreva.84.052723
|View full text |Cite
|
Sign up to set email alerts
|

Angular correlations in radiative cascades following resonant electron capture by highly charged ions

Abstract: We investigate the angular correlations between the photons emitted in the dielectronic recombination (DR) of initially hydrogenlike heavy ions. The theoretical analysis is performed based on a density-matrix approach and Dirac's relativistic theory. Special emphasis has been placed upon the effects of the higher-order, nondipole terms in the expansion of the electron-photon interaction. To illustrate these effects, we present and discuss detailed calculations for K-LL DR of initially hydrogenlike xenon, gold,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…When compared with the radiative or dielectronic capture of electrons, the Coulomb excitation is particularly suitable for studying the electron emission in strong fields as it is not disturbed by free (incident) electrons. The present analysis of the relativistic contributions to e-e interaction extends a previous study of the photon emission of HCI in which the Breit terms also lead to a different behavior in the angular distribution and polarization of the emitted x-rays [19,42] when compared with the Dirac-Coulomb theory, which was recently confirmed by experiment [20]. In contrast to photon emission, which only exhibits the integral effect of the relativistic motion of electrons, electron spectrometry enables one to access further details of the electron dynamics in strong Coulomb fields.…”
Section: Resultssupporting
confidence: 80%
“…When compared with the radiative or dielectronic capture of electrons, the Coulomb excitation is particularly suitable for studying the electron emission in strong fields as it is not disturbed by free (incident) electrons. The present analysis of the relativistic contributions to e-e interaction extends a previous study of the photon emission of HCI in which the Breit terms also lead to a different behavior in the angular distribution and polarization of the emitted x-rays [19,42] when compared with the Dirac-Coulomb theory, which was recently confirmed by experiment [20]. In contrast to photon emission, which only exhibits the integral effect of the relativistic motion of electrons, electron spectrometry enables one to access further details of the electron dynamics in strong Coulomb fields.…”
Section: Resultssupporting
confidence: 80%
“…The electron recombination with highly charged ions presents a tool for investigation of the Breit interaction. The recent studies showed that the Breit interaction may give important and even dominant contribution to the cross section of the dielectronic recombination with few-electron highly charged ions [9,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies showed that the Breit interaction may give important and even dominant contribution to the cross section of the dielectronic recombination with few-electron highly charged ions [9,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the sum each line is then weighted by the corresponding relative population of the (initially) doublyexcited state and by the relative branching ratio for the subsequent radiative decays. Here, we shall not discuss the correlations between the HS and S photons emitted in the decay of the L 1/2 L 3/2 resonance group in great detail, but point out that rather strong multipole-mixing effects can still be observed despite the averaging over all cascade transitions of this resonance group [30]. In figure 5, for example, we display the correlation function for the coincidence measurement of the HS and S photons assuming that only the spin state of the S x-rays is observed in a particular setup.…”
Section: Resultsmentioning
confidence: 99%